Adaptação transcultural e validação do instrumento Nutrition in Patient Care Survey (NIPS), no Brasil - SLEUMER, J. P. N. (2018)
Introduction: Inadequate nutritional habits are considered an important risk factor for the development of chronic noncommunicable diseases (CNCD). The physician plays an important role in modifying and improving the nutritional behavior of his patients and consequently improving of the health. In this context, it is necessary to measure, through reliable instruments, the attitude of students and physicians on nutrition in patient care, to subsidize educational interventions that will impact clinical practice. Objective: To translate, culturally adapt and validate the Nutrition in Patient Care Survey (NIPS), which assesses attitudes in nutritional care in clinical practice, to be used in the Portuguese-speaking population in Brazil. Methodology: The original NIPS version in English was initially translated into Portuguese and submitted to a cross-cultural adaptation of vocabulary and linguistic construction. This version was then retranslated into English. The questionnaire was then applied to pre-test in 30 medical students, in order to eliminate doubts about the comprehension of the questions. The final version of the adapted instrument was applied to 400 medical students. The analysis of reliability and validity has been performed using factorial analysis. Result: 400 students answered all NIPS questions and were included in the analysis. After a factorial analysis, the final structure of the scale was defined, which now has 37 items, in a likert form from 1 (totally disagree) to 05 (totally agree), divided into ten factors, different from the original scale with five factors. The internal consistency (Cronbach's alpha) for the ten factors studied was greater than 0.60 in most of them and the general alpha was greater than 0.50. In the construct validity analysis, the majority of the correlation coefficients were significant (p values <0.005). With this structure, the proposed scale presented an internal consistency understood as favorable, explaining 58.93% of students' attitudes regarding nutritional care in patient care. Conclusion: The version in Portuguese of the NIPS instrument, after an adaptation process, proved to be useful and adequate to gather information regarding the attitude of medical students in the patient's nutritional care.